Caring callers: the impact of the telephone reassurance program on homebound older adults during COVID-19. Issue 4 (2nd October 2021) - Lee, Kathy; Fields, Noelle; Cassidy, Jessica; Kusek, Venieca; Feinhals, Gretchen; Calhoun, Melanie
ABSTRACT: During the COVID-19 pandemic, older adults experienced great levels of social isolation and feelings of loneliness. We developed a telephone reassurance program, Caring Callers, to provide a weekly phone call to socially isolated older adults. Dyads were created which comprised of a Senior Companion volunteer and a homebound older adult. Using a mixed methods approach, we examined the program's impact on homebound older adults. The participants were satisfied with the program and showed a significant increase in overall health. They discussed social and emotional benefits of the program and other benefits that they gained from community resources. Due to the vulnerability of the participants, this telephone-based intervention seemed feasible without technological barriers. It is critical that aging service providers recognize the resourcefulness and relatability of older adult volunteers and utilize them to continue to support socially isolated older adults during an unprecedented event affecting people's isolation.